The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1103/physrevb.71.214425
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal in elongated Fe nanoparticles

Abstract: Magnetization reversal of individual, isolated high-aspect-ratio Fe nanoparticles with diameters comparable to the magnetic exchange length is studied by high-sensitivity submicron Hall magnetometry. For a Fe nanoparticle with diameter of 5 nm, the magnetization reversal is found to be an incoherent process with localized nucleation assisted by thermal activation, even though the particle has a single-domain static state. For a larger elongated Fe nanoparticle with a diameter greater than 10 nm, the inhomogene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
(50 reference statements)
2
13
0
1
Order By: Relevance
“…13 However, even in SD nanoparticles, the magnetization reversal can be quite complex, involving thermally activated incoherent processes. 14 The VS-SD crossover itself is fascinating. For example, recently Jausovec et al have proposed that a third, metastable, state exists in 97 nm permalloy nanodots, based on minor loop and remanence curve studies.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, even in SD nanoparticles, the magnetization reversal can be quite complex, involving thermally activated incoherent processes. 14 The VS-SD crossover itself is fascinating. For example, recently Jausovec et al have proposed that a third, metastable, state exists in 97 nm permalloy nanodots, based on minor loop and remanence curve studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that near the SD-VS phase boundary, both phases can be stabilized and conversion from one to the other can be triggered by thermal activation or magnetic field cycling. 8,10 Therefore, it is not always reliable to use the nanomagnet remanent magnetic configuration or the shape of the hysteresis loop to determine the presence of VS. 14 On the other hand, the irreversible events associated with vortex nucleation and annihilation are clear signatures of VS. They can be used to track the nanomagnets that reverse via VS, regardless whether the remanent state is VS or not.…”
mentioning
confidence: 99%
“…There have been extensive theoretical and experimental studies on SD-VS phase diagrams as a function of nanomagnet dimensions. 6,[8][9][10] Typically, e.g., in isotropic circular dots, the VS evolution from positive saturation starts with an abrupt magnetization drop at a positive nucleation field, followed by a flux closure state with zero remanence and finally the vortex annihilation at a negative field. 6 Observation of the VS at remanence using magnetic microscopy 5 has indeed become a common practice.…”
mentioning
confidence: 99%
“…These measurements have been carried out in a gradiometry setup where the Hall voltage at the cross carrying the sample is compensated by applying a current of same magnitude but opposite sign through an empty reference cross. This results in a differential signal ∆V H solely due to the sample's magnetization [9,10]. The data in since for multiple walls the magnetization reversal wouldn't be expected to follow only a few distinct paths.…”
Section: Resultsmentioning
confidence: 99%